Good Corporate Governance And Corporate Social Responsibility On Company Value With Financial Performance - Yana Fajriah; Edy Jumady; Ardiansyah Halim (Jurnal Akuntansi, 2022)
This study was conducted to see how much influence the variables of Good corporate governance and corporate social responsibility have on firm value with financial performance as the intervening variable. This type of research is quantitative research, which uses SmartPLS to analyze data by taking annual financial reports from 2017- 2019 from pharmaceutical sector manufacturing companies on the Indonesian stock exchange. The sample of this research is 11 companies. The results of the study show that the 4 indicators that have a significant positive effect on GCG are: Managerial Ownership, Institutional Ownership, Independent Commissioner and Audit Committee on Firm Value (Tobin's) and Financial Performance (ROA), while CSR has a significant positive effect on Financial Performance (ROA) but CSR has a positive and insignificant effect on Firm Value (Tobin's), Financial Performance (ROA) has a positive and significant effect on Firm Value (Tobin's), and Financial Performance (ROA) can mediate GCG and CSR has a positive and significant effect. The results of this study can also be used for the company to determine the ability to manage the company in generating profits and achieving success in the company in the future, also as a source of information and reference for further researchers in conducting research on topics related to this research, either continuing or complementary.